Life-long reduction in myomiR expression does not adversely affect skeletal muscle morphology - Vechetti, Ivan J. [UNESP]; Wen, Yuan; Chaillou, Thomas; Murach, Kevin A.; Alimov, Alexander P.; Figueiredo, Vandre C.; Dal-Pai-Silva, Maeli [UNESP]; McCarthy, John J. (Nature Publishing Group, 2019)
We generated an inducible, skeletal muscle-specific Dicer knockout mouse to deplete microRNAs in adult skeletal muscle. Following tamoxifen treatment, Dicer mRNA expression was significantly decreased by 87%. Wild-type (WT) and Dicer knockout (KO) mice were subjected to either synergist ablation or hind limb suspension for two weeks. There was no difference in muscle weight with hypertrophy or atrophy between WT and KO groups; however, even with the significant loss of Dicer expression, myomiR (miR-1, -133a and -206) expression was only reduced by 38% on average. We next aged WT and KO mice for similar to 22 months following Dicer inactivation to determine if myomiR expression would be further reduced over a prolonged timeframe and assess the effects of myomiR depletion on skeletal muscle phenotype. Skeletal muscle Dicer mRNA expression remained significantly decreased by 80% in old KO mice and sequencing of cloned Dicer mRNA revealed the complete absence of the floxed exons in KO skeletal muscle. Despite a further reduction of myomiR expression to similar to 50% ofWT, no change was observed in muscle morphology between WT and KO groups. These results indicate the life-long reduction in myomiR levels did not adversely affect skeletal muscle phenotype and suggest the possibility that microRNA expression is uniquely regulated in skeletal muscle.